Heterogeneity and the equitable rate of interest - Riccardo Masolo (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2023)
The equitable rate of interest represents a benchmark to evaluate the cross-sectional effects of monetary policy. I define it as the real rate of interest that minimizes the welfare losses associated to cross-sectional heterogeneity, under flexible prices. In a large class of models, it can be expressed as the payoff of a suitably chosen portfolio. In a Two-Agent New Keynesian model the deviations of the optimal policy prescription, relative to a Representative-Agent benchmark, can be traced back to the equitable rate gap: the difference between prevailing real rates and the equitable rate. This parallels the way in which the natural rate is the reference stick to evaluate the stance of monetary policy with regards to aggregate stabilization. Indeed, the difference between the natural rate and the equitable rate marks the tradeoff between aggregate and cross-sectional stabilization, faced by a welfare-maximizing policymaker.
Keywords: E31; E52; 330; Monetary Policy; Heterogeneous Agents; Optimal Policy